Functional Interpretation Of Structure Of Bacillus Thuringiensis Dendrolimus T84a1-Cry1aa9 Toxin Using Computational Modeling Approach - S. KASHYAP, (International Journal of Pharma and Bio Sciences, 2012)
The theoretical homology based structural model of Cry1Aa9 δ-endotoxin produced by Bacillus thuringiensis dendrolimus T84A1was predicted using the Cry1Aa template (Resolution 2.25Å). The Cry1Aa9 resembles the template structure by sharing a common three domains extending conformation structure responsible in pore-forming and specificity determination. The novel structural differences found are presence of β0 and β12b, absence of α7b, β1a, α9a, β9 and α11a. These increments of 3D structure information will be helpful in the design of domain swapping experiments aimed at improving toxicity, and will help in elucidation of the common mechanism of toxins action.